Psychological effects of the practice of Pilates Method in a university sample - Herrera-Gutiérrez, Eva; Olmos-Soria, Marina; Brocal-Pérez, David (Anales de Psicología / Annals of Psychology, 2015)
The overall purpose of this research was to test the possible psychological effects of the practice of Pilates and, in particular, the effect on the degree of anxiety experienced. This is a method of physical training aimed at improving postural hygiene and psychological well-being, highly recommended today by health professionals, both for people with diagnosed diseases and for preventive level. So far, the physical and psychological benefits associated with regular physical activity practice have already been demonstrated. However, only a few studies have investigated the specific effects of the Pilates Method. This paper examined the anxiety (state and trait) in a sedentary group and in another group of usual practitioners of this method (staff, students, and users of sports facilities at the University of Murcia, Spain). The State-Trait Anxiety Inventory (STAI) of Spielberger, Gorsuch and Lushene (2002) was used to assess anxiety. The implications that the results of this work can have from the perspective of health promotion in the university are discussed, as well as its contribution to public health.